Comparative analysis of speed and strength among athletes of different events - Singh3, Ram Krishan1*, Manoj Yadav2, Dr. Vikram (International Multidisciplinary Research Journal, 2011)
Background:Ã‚Â  The purpose of the study was to compare the speed & strength level among the athletes of different events. Methods: For the present study 10 sprinters, 10 middle & 10 long distance runners (male) were selected randomly from C.S.J.M. University, Kanpur. Their age ranging from 18-25years. 50 meter Dash was used to measure the speed & leg lift Dynamometer for strength. The data was analyzed by applying One Way Analysis of Variance (ANOVA) technique to compare speed & strength level among athletes of different events. The level of significance was set at 0.05 Results: The result of the present study has proved that there was no significant difference found among sprinters, middle distance runners and long distance runners in case of speed. The speed ability has found at different level in the athletes different events. In case of strength there was significant difference found among sprinters, middle distance runners and long distance runners .Conclusion: In the light of the findings, it was concluded that. The result of the study indicated that the speed ability of the Sprinters has dominated on the middle & long distance runners. But no significant difference found among them. While other physical characteristic, strength ability of long distance runners has overcome on the sprinters & middle distance runners at different level in different events of the athletes.